Electronically induced modification of thin layers on surfaces: Electronic Processes in Cryocrystals - Bauer, U.; Neppl, S.; Menzel, D.; Feulner, P.; Shaporenko, A.; Zharnikov, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Interactions of thermally and electronically stimulated reactions in thin layers on surfaces are investigated. For self-assembled monolayers, thermal activation promotes many processes primarily induced by electronic excitations. We demonstrate that the film temperature is an important parameter for steering these reactions towards different final products. Using chemisorbed water on Ru(001) as an example, we investigate how the products of an irradiation induced reaction catalyze thermally stimulated dissociation of water molecules.